Reinforcing information literacy development through a subject-focused resource-based project - Yu, Halida; Abrizah, Abdullah; Rafedzi, Ezza Rafedziawati Kamal; Abdullah, Siti Nurul Maryam (SAGE Publications, 2018)
This paper discusses the findings of research investigating the implementation of a resource-based school history project in Malaysian secondary schools. It seeks to understand how the project contributes towards students’ information literacy development. The study took place in selected secondary schools in Kuala Lumpur, Malaysia. A total of 23 students and 5 teachers from four schools participated in the study, employing (a) student focus group interviews, (b) teacher individual interviews, (c) observation, and (d) document analysis as the data collection techniques. In general, although the history project is considered a “research” project by teachers and students, it is found to be a cursory information-gathering and information-compilation type of assignment, which is fully guided by the project guidelines or instructions. While teachers employ a mixture of teaching approaches in the project instruction, the efforts are concentrated on subject matter-related issues such as subject content and project instructions fulfillment. The larger learning experience such as information literacy and learning skills development, as well as research and report writing enhancement, appear to be overlooked in the instructions. The findings also show that (a) information literacy is loosely defined, (b) the “information gathering and information compilation” of the project task is of a superficial nature, and (c) inadequate guidance from teachers has resulted in low information literacy development among students. This study highlights the critical need to address information literacy in the education system, design resource-based assignments with a clear information literacy focus, and the importance of support from teachers for successful development. It provides a foundation for further research on the development of information literacy-focused resource-based school project assignments.